Urogenital surgery in farm animals. Issue 2 (4th February 2016) - Hallowell, Gayle; Potter, Tim
Abstract : The types of urogenital conditions observed in large animals are both species and function dependent, with very different diseases being seen in commercial stock compared with small groups of animals of the same species. This article focuses on conditions that can be managed surgically, discussing the decision‐making process for conditions such as urinary tract obstruction, bladder prolapse and pyelonephritis, along with techniques for caesarean section, vasectomy and castration.